The Effect Of Value-Added Tax (Vat) Rate Increase Policy On Inflation Rate, Public Consumption, And Welfare In Indonesia - Mega Orvala Puteri; Lipa Alipah; Irwan Sutirman Wahdiat (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to determine the impact of an increase in the Value Added Tax (VAT) rate on the inflation rate, public consumption patterns, and welfare in Indonesia. VAT is one of the important tools in fiscal policy that contributes greatly to state revenue. The policy of increasing the VAT rate from 11% to 12% in Indonesia is designed to strengthen state revenue in order to support fiscal expenditure, but this policy also has the potential to affect the inflation rate, people's purchasing power, and general economic welfare. This study adopts a quantitative approach by utilizing secondary data in the form of inflation rates, public consumption, state revenue, and VAT rates for the period 2019 to 2023, obtained from the Central Statistics Agency (BPS). The analytical method used is linear regression, which is a hypothesis test to identify the relationship between variables. The results show that the increase in VAT rates has a positive but insignificant effect on inflation and public consumption. On the other hand, the increase in VAT rate has a positive and significant impact on state revenue, with a contribution of 97.4% to the increase in total tax revenue. This finding indicates that although people's purchasing power has not decreased drastically, the government still needs to consider the long-term impact of this policy on economic welfare.